2016
DOI: 10.1016/j.immuni.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Drive Autoimmune Arthritis by Promoting Differentiation and Migration of Peyer’s Patch T Follicular Helper Cells

Abstract: SUMMARY Gut microbiota profoundly affect gut and systemic diseases, but the mechanism whereby microbiota affect systemic diseases is unclear. It is not known whether specific microbiota regulate T follicular helper (Tfh) cells, whose excessive responses can inflict antibody-mediated autoimmunity. Using the K/BxN autoimmune arthritis model, we demonstrated that Peyer’s patch (PP) Tfh cells were essential for gut commensal segmented filamentous bacteria (SFB)-induced systemic arthritis despite the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
225
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(242 citation statements)
references
References 41 publications
9
225
0
1
Order By: Relevance
“…We previously established a model to study the effect of SFB in autoimmune development by gavaging SFB-containing (simplified as SFB+ hereafter) feces into SFB negative (SFB−) mice housed in our specific-pathogen-free animal facility (Teng et al, 2016). Arthritis development plateaus on or beyond day 14 post-SFB gavage in this model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established a model to study the effect of SFB in autoimmune development by gavaging SFB-containing (simplified as SFB+ hereafter) feces into SFB negative (SFB−) mice housed in our specific-pathogen-free animal facility (Teng et al, 2016). Arthritis development plateaus on or beyond day 14 post-SFB gavage in this model.…”
Section: Resultsmentioning
confidence: 99%
“…The low concordance rate of RA in monozygotic twins (~20%) suggests that environmental factors play a key role in RA (Seldin et al, 1999). We have previously demonstrated that the gut microbiota, segmented filamentous bacteria (SFB), act as an environmental cue to enhance autoimmune arthritis by inducing T helper 17 (Th17) and T follicular helper (Tfh) cells (Teng et al, 2016; Wu et al, 2010). A strong interest has emerged in characterizing the role of gut microbiota in lung disease, a gut-lung axis of communication, exemplified by gut microbiota’s impact on diseases including asthma, chronic obstructive pulmonary disease (COPD), and respiratory infections (Budden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, SFB colonization promotes disease in the K/BxN mouse model of RA, in part by inducing SI-LP Th17 cells that emigrate from the gut to the spleen, where they promote production of autoantibodies against glucose-6-phosphate isomerase (24,41). Such autoantibodies in and of themselves can induce arthritis and, after they reach high levels, require no further input from Th17 cells.…”
Section: B Adolescentis Exacerbates Autoimmune Arthritis In a Mouse mentioning
confidence: 99%
“…Although the T H 17 cells induced by SFB are noninflammatory, in the right major histocompatibility complex (MHC) background of autoimmune predisposition, they can provide help for B-cell-dependent autoimmune arthritis. susceptibility, the SFB T H 17 subset can provide the necessary germinal center help to generate arthritis via autoantibodies (Maloy et al 2003;Wu et al 2010;Teng et al 2016). Given the local focus of most mucosal immune responses induced by the microbiota, the most promising opportunities are to use these responses to manipulate the system to dampen proinflammatory responses from its more aggressive members.…”
Section: Context Responsesmentioning
confidence: 99%